A comparative study in estimating the maximum oxygen consumption between the Bruce and Cooper test for young basketball players - Al-Shammari, Elaf Ahmad Mohammed; Mahmood , Zaid Shakir; Mahmood , Zaid Shakir (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to make a comparison in estimating the maximum oxygen consumption between the tests of Bruce and Cooper for young basketball players aged 17 years. As the tremendous functional variables that basketball players reached led the researchers to investigate and research the finer things in matters by relying on laboratory devices to study functional variables. However, the difficulty of obtaining these devices and how to use them in addition to their high price prompted researchers to find equations for indirect measurement in order to facilitate the provision of information to workers in the sports field in order to determine the levels of their teams on the one hand and evaluate the level of their training curricula on the other hand. As for the second chapter. It included determining the appropriate approach for the research and it was the descriptive approach. As for the research sample, it was 4 young basketball players at the age of (17) years. The process of measuring the research variables was done by using the standardized equations for determining and measuring the maximum oxygen consumption represented by the Bruce and Cooper equations. The researchers also dealt with tools and means of collecting information and exploratory experience, as well as the use of the statistical package (SPSS) to process data. The third chapter included presenting, analyzing and discussing the results of the research sample, as the results showed that there were no significant differences between Bruce and Cooper tests in estimating the maximum oxygen consumption. As for the conclusion, the researchers concluded that there was no significant difference between the Bruce and Cooper tests in estimating the maximum oxygen consumption, and this is evidence of the correctness of the work at any of the rates adopted in the research. Oxygen as well as the necessity of recommending researchers to conduct extensive studies in codifying predictive equations and studying them before working with them in order to ensure their validity and suitability with the Iraqi environment.